Does septum resection improve reproductive outcomes for women with a septate uterus? A systematic review and meta-analysis - Liu, Chang; Liao, Zhiqi; Gong, Xueqi; Chen, Yinwei (Frontiers in Endocrinology, 2024)
Objective To investigate whether incising the septum facilitates reproductive outcomes for patients with a septate uterus compared to expectant management. Methods Research was retrieved from three electronic databases: PubMed, Embase, and the Cochrane Library, with no time or language restrictions. Two authors independently selected the articles and extracted data regarding study characteristics, quality, and results. A random-effects model was employed, and summary risk ratios (RR) with 95% confidence intervals (CI) were calculated. Results A total of 468 patients from two randomized controlled trials and one cohort study were included in the systematic review and meta-analysis. Pooled results showed that septum resection did not improve the live birth rate for patients with a septate uterus (RR = 0.84, 95% CI = 0.56 – 1.25, P = 0.39). Additionally, no significant differences were found between the septum resection and expectant management groups in terms of clinical pregnancy (RR = 1.08, 95% CI 0.81 – 1.44, P = 0.60), abortion (RR = 1.99, 95% CI 0.80 – 4.98, P = 0.14), and preterm delivery rates (RR = 0.99, 95% CI 0.42 – 2.31, P = 0.98). Conclusion Our data provide clear evidence that septum resection does not improve the reproductive outcomes of patients with a septate uterus. These findings might be useful for revising current clinical guidelines.